Participatory diagnostic for scaling a decision support tool for rice crop management in northern Nigeria. Issue 1 (2nd January 2021) - Zossou, Espérance; Saito, Kazuki; Assouma-Imorou, Alidou; Ahouanton, Kokou; Tarfa, Bitrus Dawi
ABSTRACT: RiceAdvice is a decision support tool with potential to improve rice productivity and profitability of smallholder farmers in sub-Saharan Africa. A rapid appraisal of agricultural innovation systems approach was used to assess opportunities and constraints in scaling the tool. Qualitative and quantitative data were collected through semi-structured interviews, multi-stakeholder workshop, and questionnaires distributed to 368 farmers in Kano State, northern Nigeria. Results show that scaling RiceAdvice requires: (i) improved access to financial and input supply services through partnerships; (ii) identifying and testing business models where RiceAdvice can be used; and (iii) a dissemination approach where female service providers reach female farmers.